2015
DOI: 10.1037/spy0000041
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of perfectionism among self-identified perfectionists in sport and the performing arts.

Abstract: (2015) A qualitative study of perfectionism among self-identified perfectionists in sport, dance, and music. Sport, exercise and performance psychology, 44 (4). pp. 237-253. When adopting any measure of perfectionism to examine the characteristic in sport or the 2 performing arts, researchers make assumptions regarding its core features and, sometimes, its 3 effects. So to avoid doing so, in the current study we employed qualitative methods to examine 4 the accounts of self-identified perfectionists. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 51 publications
7
70
0
1
Order By: Relevance
“…These findings are in line with previous research, which have consistently found EC to be associated with maladaptive motivational processes . One plausible explanation of the occurred relationship between EC and each basic need frustration is the biased mind‐set of EC, which in turn influence the perception of and reaction to environmental requests . The way EC relates to performance evaluations (ie, self‐critical and devaluate) may negatively influence the need for competence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in line with previous research, which have consistently found EC to be associated with maladaptive motivational processes . One plausible explanation of the occurred relationship between EC and each basic need frustration is the biased mind‐set of EC, which in turn influence the perception of and reaction to environmental requests . The way EC relates to performance evaluations (ie, self‐critical and devaluate) may negatively influence the need for competence.…”
Section: Discussionsupporting
confidence: 91%
“…22,27,35 One plausible explanation of the occurred relationship between EC and each basic need frustration is the biased mind-set of EC, which in turn influence the perception of and reaction to environmental requests. 60 The way EC relates to performance evaluations (ie, self-critical and devaluate) may negatively influence the need for competence. Moreover, the need for competence might also be frustrated by the way the EC mind-set monitors for critique and disapproval in feedback from others, and thus, further nurture feelings of inferiority and low self-worth.…”
mentioning
confidence: 99%
“…interpersonal versus intrapersonal dimensions), and the extent to which adaptive and maladaptive aspects of perfectionism are distinguished. 3 Given that socially prescribed features of perfectionism may be internalised and form part of a person's self-imposed perfectionism, 4 we sought optimal parsimony in this study by operationalising perfectionism based solely on intrapersonal dimensions. Along these lines, we drew on the work of others 5,6 and focused on a single feature of each superordinate dimension of perfectionism.…”
Section: Introductionmentioning
confidence: 99%
“…Há também um grande risco de comportamentos obsessivos e transtornos alimentares entre artistas, por conta de uma estrutura corporal muito específica que deve ser alcançada e mantida em determinadas ocupações (Hays, 2002). É importante enfatizar que, ao contrário do que pode se pensar no senso comum, o perfeccionismo e a obsessão não são necessariamente adaptativos em contextos de alta performance, uma vez que a inflexibilidade e comportamentos autodestrutivos estão associados a esses traços (Hill, Mallinson--Howard, & Jowett, 2018;Hill, Witcher, Gotwals, & Leyland, 2015).…”
Section: Mundo Artísticounclassified